Preparation method of nano titanium carbide particles

Through the grading heating pyrolysis method and dynamic atmosphere regulation, combined with the precursor synthesis and post-treatment steps, the problem of stable preparation of nano-titanium carbide particles is solved, and the preparation of nano-TiC particles with high purity and uniform particle size distribution is achieved, which improves process controllability and performance.

CN119774615AActive Publication Date: 2025-04-08ZHUZHOU HONGDA IND CO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411976942.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

It is difficult for the prior art to stabilize the preparation of nano-titanium carbide particles with high purity and uniform particle size distribution at the nano level, and traditional processes are prone to particle agglomeration, impurity introduction and high energy consumption.

Method used

The formation process of nano-TiC particles is finely controlled by precursor synthesis, pretreatment, graded heating pyrolysis, selective etching of excess carbon layer and post-treatment steps.

Benefits of technology

Accurate control of nano-TiC particle size and grain distribution is achieved, reducing oxide inclusion and free carbon content, improving the purity and performance of the product, and significantly improving process controllability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774615A_ABST
    Figure CN119774615A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of carbide materials, in particular to a preparation method of nano titanium carbide particles. The method comprises the following steps: reacting a titanium source compound with an organic ligand in a solvent at a low temperature to obtain an MOF precursor, carrying out graded heating pyrolysis, introducing H2 / Ar mixed gas at a low-temperature stage for mild reduction, carrying out intermittent pressure reduction and exhaust at a medium-temperature stage to remove small-molecule products, carrying out short-time exposure by using an extremely-low-concentration hydrocarbon gas pulse at a high-temperature stage, and switching back to a protective atmosphere to obtain the MOF precursor. The preparation method comprises the following steps of: firstly, preparing a TiC nano-crystal particle into a high-temperature zone, so that ordered generation and particle size inhibition of TiC nano-crystal particles are realized, the particle size of TiC is concentrated at 10-50nm, and finally, a micro-reducing dilute hydrogen atmosphere is introduced into a medium-temperature zone to selectively etch excessive amorphous carbon, so that the content of free carbon is remarkably reduced, and the purity and crystallinity of a product are improved. The nano TiC powder with uniform distribution and controllable granularity is obtained, and a high-quality precursor raw material is provided for manufacturing of a high-performance material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbide material preparation, and in particular to a method for preparing nano titanium carbide particles. Background Art

[0002] Titanium carbide (TiC) is a typical representative of the transition metal carbide family. It has attracted widespread attention for its high melting point, high hardness, good strength and chemical stability at high melting temperatures. In traditional applications, TiC is often used as a wear-resistant coating, cemented carbide additive phase and high-temperature resistant structural material. With the rapid development of nanoscience and technology, nanoscale TiC particles (particle size is generally in the range of 1-100 nanometers) have shown more potential applications due to their ultra-high specific surface area, excellent surface activity and unique size effect. For example, nano-TiC can be used as a reinforcing component of superhard materials, significantly improving the mechanical properties and high-temperature stability of metal-based and ceramic-based composites; it can also be used in cutting-edge fields such as catalysis and energy storage (such as electrode materials).

[0003] However, the stable preparation of nano-TiC still faces technical difficulties: the traditional process of preparing TiC powder mostly relies on high-temperature carbon thermal reduction, chemical vapor deposition (CVD) or self-propagating high-temperature synthesis (SHS) and other methods. These methods are relatively mature on a macro scale, but it is not easy to stably control the particle size at the nanoscale and obtain uniformly distributed, high-purity TiC powder at the same time. High-temperature processes often lead to particle agglomeration, excessive growth, and the introduction of impurity phases; while low-temperature chemical methods such as wet chemistry or sol-gel have certain potential in particle size control, the process is complex and sensitive to the purity of the precursor and operating conditions, which can easily lead to other impurity elements remaining in the product or make it difficult to scale up production.

[0004] In recent years, some new preparation routes have gradually attracted attention. For example:

[0005] 1. Precursor thermal decomposition method: Use organic titanium compounds and carbon sources to control the reaction conditions at a lower temperature so that the decomposition products are directly converted into nano-TiC.

[0006] 2. Sol-gel and subsequent heat treatment: The titanium salt sol and the organic carbon source are uniformly mixed and gelled, and then the Ti and C components in the gel are converted into TiC in situ under a controlled atmosphere and a temperature program.

[0007] 3. Mechanical alloying and subsequent reaction sintering: Titanium powder is fully mixed with carbon black or organic carbon source through high-energy ball milling and refined to nanometer scale, and TiC nanocrystals are generated at low temperature under appropriate heat treatment conditions.

[0008] 4. Plasma-assisted synthesis: Plasma chemical reactions are used to rapidly decompose and react precursors, achieving instantaneous high temperature and rapid cooling, which is beneficial to the nucleation and growth control of nano-scale TiC.

[0009] These emerging methods complement traditional technical routes and aim to achieve the following goals: precisely control the particle size and grain distribution of TiC nanoparticles; reduce preparation temperature and energy consumption, reduce grain growth and agglomeration; effectively control the impurity phase content and oxygen content in the product, and improve purity and performance; achieve a balance between production scale and cost, and provide feasibility for large-scale industrialization.

[0010] In this context, the technical development for the preparation of nano-titanium carbide particles requires not only the selection of suitable precursors and carbon sources, but also the optimization of mixing dispersion, atmosphere control, heating program and insulation system to obtain nano-TiC products with high purity, uniform particle size distribution and good dispersibility, so as to better meet the growing performance requirements in the fields of cemented carbide reinforcement, wear-resistant coating preparation, turbine blade toughening and emerging catalytic materials. Summary of the invention

[0011] In view of the above problems, the present invention aims to provide a method for preparing nano-titanium carbide particles, comprising the following steps:

[0012] S1. Precursor synthesis steps:

[0013] The titanium source compound and the organic ligand are mixed and reacted in a solvent, and the reaction temperature and reaction time are controlled to form a titanium-containing metal organic framework (MOF) precursor;

[0014] S2, Precursor pretreatment steps:

[0015] The titanium-containing metal organic framework (MOF) precursor obtained in step S1 is centrifuged, washed and dried at a temperature of 60 to 120° C. for 6 to 24 hours to obtain a uniformly refined MOF precursor powder;

[0016] S3, step of graded heating and pyrolysis:

[0017] The dried MOF precursor powder is placed in a heating furnace, with protective gas as the base gas, and a trace amount of control gas is introduced at a specific stage to achieve dynamic atmosphere control, complete graded heating pyrolysis, and obtain a fine and uniform distribution of nano-TiC grains;

[0018] S4, step of selectively etching excess carbon layer:

[0019] After the furnace temperature is naturally cooled to a predetermined temperature, the treatment furnace is filled with protective gas, and then H2 gas is introduced into the furnace, with a volume fraction of H2 of 5 to 20%, to obtain a slightly reducing dilute hydrogen environment;

[0020] After heating to a predetermined temperature, the temperature is maintained, so that H2 reacts slightly with amorphous carbon on the solid surface under heating conditions, thereby selectively etching the excess carbon layer and reducing the free carbon content;

[0021] S5, post-processing steps:

[0022] After the step of selectively etching the excess carbon layer is completed, the protective gas is charged and discharged multiple times to remove the residual H2 gas. After the furnace temperature is cooled to room temperature, the furnace is opened to take out the material, and nano-titanium carbide particles of a predetermined size are obtained after sieving.

[0023] Further, step S1 specifically includes: a reaction temperature of 25 to 80° C., a reaction time of 12 to 48 hours; a solvent of a mixture of one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP) or dimethyl sulfoxide (DMSO);

[0024] The titanium source is TiCl4 or Ti(OR)4, wherein R is a C1-C4 alkyl group, and the organic ligand is selected from a multidentate ligand containing a carboxyl group, a hydroxyl group or a nitrogen coordination group; the grain size of the obtained titanium-containing metal organic framework (MOF) precursor is 100-500nm.

[0025] Furthermore, step S3 specifically includes:

[0026] S31, low temperature desorption and atmosphere control stage:

[0027] The temperature is raised to a predetermined temperature and then maintained, and then a H2 / Ar mixed gas is introduced to reduce the surface of the titanium precursor in the titanium-containing metal organic framework (MOF) and reduce the impurity oxygen content;

[0028] S32, medium temperature orderly deconstruction and precursor phase regulation stage:

[0029] The temperature is raised to a predetermined temperature again and then kept warm, during which the total system pressure is intermittently reduced to discharge small molecular gaseous products;

[0030] S33, high temperature directional carbonization and particle size suppression stage:

[0031] The temperature is raised to the predetermined temperature again and then kept warm. In the second half of the warm-keeping period, hydrocarbon gas is quantitatively introduced at a rate of <0.5 vol%. After a short exposure, the protective atmosphere is switched back.

[0032] Furthermore, step S31 is specifically as follows:

[0033] The temperature is raised from room temperature to 200-300°C at a heating rate of 1-5°C / min, and kept at this temperature for 0.5-2 hours to remove the residual solvent in the pores;

[0034] In the second half of the insulation, 0.1-1 vol% H2 / Ar mixed gas can be introduced in a pulsed manner to slightly reduce the surface of the titanium precursor in the titanium-containing metal organic framework (MOF) and reduce the impurity oxygen content, thereby reducing oxide inclusions for the subsequent carbonization process.

[0035] Furthermore, step S32 is specifically as follows: continue to raise the temperature to 500-700° C. at a rate of 3-10° C. / min, and keep the temperature for 1-3 hours, and intermittently reduce the total pressure of the system during the heat preservation period to continuously discharge small molecular gaseous products.

[0036] Furthermore, in step S32, intermittently reducing the total system pressure means: pumping the pressure to 50-80% of the current original pressure every 30 minutes, and maintaining the pumping for 5-10 minutes, then stopping the pumping, and pumping again after 30 minutes.

[0037] Further, step S33 is specifically as follows: heating to 800-1200°C at a rate of 5-10°C / min, maintaining the temperature for 2-6 hours, allowing Ti and carbon to react in situ to form TiC nano-grains, and introducing hydrocarbon gas quantitatively at a concentration of <0.5vol%) in the second half of the insulation period, and switching back to pure protective atmosphere after a short exposure of 5-10 minutes; the hydrocarbon gas is CH4, C2H2, or a mixture of CH4 and C2H2.

[0038] Furthermore, step S5 is specifically as follows:

[0039] S51, after the furnace temperature is naturally cooled to 100° C., the treatment furnace is filled with protective gas, and then H2 gas is introduced into the furnace, with a volume fraction of H2 of 5 to 20%, to obtain a slightly reducing dilute hydrogen environment;

[0040] S52. Starting from 100°C, heat to 300-500°C at a heating rate of 3-10°C / min, and then keep warm for 0.5-2 hours to allow H2 to react with amorphous carbon on the solid surface under heating conditions, selectively etch the excess carbon layer, and reduce the free carbon content.

[0041] Furthermore, the protective gas is one of pure argon, pure nitrogen, and a mixture of nitrogen and argon.

[0042] The invention also provides a nano titanium carbide particle, which is prepared by the method described.

[0043] Beneficial Effects

[0044] The solution of the present invention realizes fine control of the precursor structure deconstruction and TiC phase formation process through the organic combination of graded temperature increase and dynamic atmosphere control, and has the following beneficial effects:

[0045] 1. Precise control of particle size and distribution: Introducing extremely low concentrations of hydrocarbon gas during the high-temperature carbonization stage, using short-term pulse exposure and rapid switching to a protective atmosphere, effectively inhibiting the excessive growth of TiC grains, so that the product nanoparticle size is concentrated in the range of 10 to 50 nm and the distribution is more uniform.

[0046] 2. Reduce oxide inclusions: Introducing a trace amount of H2 / Ar mixed gas and intermittent pressure reduction exhaust during the low-temperature desorption and medium-temperature regulation stages not only helps to remove residual solvents and small molecule products from MOF, but also can slightly reduce the surface of Ti species and reduce the oxygen content, which effectively reduces the inclusion of oxide impurities in TiC and improves the purity and crystallinity of the product.

[0047] 3. Carbon content optimization and interface purification: In the final etching step, the excess amorphous carbon is selectively removed in a slightly reducing dilute hydrogen environment, which significantly reduces the free carbon content in the final product, thereby obtaining TiC nanopowders with higher purity and cleaner interfaces, thereby enhancing its application potential in high-performance materials.

[0048] 4. Improved process controllability and stability: By adopting multi-stage temperature rise, dynamic atmosphere and pressure control strategies, process parameters can be flexibly adjusted according to target particle size and purity requirements. In batch production, it is easier to obtain stable and repeatable product quality and performance.

[0049] In summary, the present invention achieves high purity, uniform particle size distribution and effective microstructure optimization of TiC nanopowders through precise process parameter setting and atmosphere control, providing a high-quality raw material foundation for the practical application of nano-titanium carbide materials in high-end equipment, functional coatings, cemented carbides and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is a schematic diagram of the method flow of the present invention;

[0051] Figure 2 This is a scanning electron microscope (SEM) photo of nano-titanium carbide particles prepared by the method of the present invention;

[0052] Figure 3 The following is a transmission electron microscope (TEM) photograph of nano-titanium carbide particles prepared by the method of the present invention. DETAILED DESCRIPTION

[0053] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0054] Embodiment 1

[0055] according to Figure 1-Figure 3As shown, this embodiment provides a method for preparing nano titanium carbide particles, comprising the following steps:

[0056] S1. Precursor synthesis steps:

[0057] A titanium source compound and an organic ligand are mixed and reacted in a solvent, the reaction temperature is controlled to be 25 to 80° C., and the reaction time is 12 to 48 hours to form a titanium-containing metal organic framework (MOF) precursor; the titanium source is TiCl4 or Ti(OR)4 (R is a C1 to C4 alkyl group), and the organic ligand is selected from a multidentate ligand containing a carboxyl group, a hydroxyl group or a nitrogen coordination group; the obtained MOF grain size is 100 to 500 nm;

[0058] S2, Precursor pretreatment steps:

[0059] The titanium-containing metal organic framework (MOF) precursor obtained in step S1 is centrifuged, washed and dried at a temperature of 60 to 120° C. for 6 to 24 hours to obtain a uniformly refined MOF precursor powder;

[0060] S3, step of graded heating and pyrolysis:

[0061] The dried MOF powder is placed in an overall protective environment, based on an inert atmosphere (such as Ar or N2), while introducing a trace amount of regulating gas or realizing dynamic atmosphere switching at a specific stage to obtain a finer and controllable distribution of nano-TiC grains. The specific process is as follows:

[0062] a. Low temperature desorption and atmosphere control stage:

[0063] The temperature is raised from room temperature to 200-300°C at a heating rate of 1-5°C / min and maintained at this temperature for 0.5-2 hours. This not only removes the residual pore solvent, but also allows the introduction of a very low flow rate (0.1-1 vol%) of H2 / Ar mixed gas in a pulsed manner in the second half of the insulation to slightly reduce the surface of the titanium precursor in the MOF and reduce the impurity oxygen content, thereby reducing oxide inclusions for the subsequent carbonization process.

[0064] b. Medium temperature orderly deconstruction and precursor phase regulation stage:

[0065] Continue to raise the temperature to 500-700°C at 3-10°C / min, and keep it at this temperature for 1-3 hours. In addition to decomposing the organic ligand into carbonaceous precursors, the total system pressure is intermittently reduced during the insulation period (such as reducing the pressure to 50-80% of the original every 30 minutes and maintaining it for 5-10 minutes) to promote the timely extraction of small molecular gaseous products (such as H2, CO, CO2). This can reduce the residual gas partial pressure and the tendency of disordered aggregation of carbon residues, thereby obtaining a more uniformly distributed nanocarbon precursor structure and promoting Ti to be evenly distributed in the carbon network at a lower valence state.

[0066] c. High temperature directional carbonization and particle size suppression stage:

[0067] The temperature is raised to 800-1200°C at a rate of 5-10°C / min, and kept at this temperature for 2-6 hours, so that Ti and carbon react in situ to form TiC nanoparticles. The innovation lies in that at this stage, hydrocarbon gases such as CH4 or C2H2 can be quantitatively introduced at extremely low concentrations (<0.5vol%) by periodically changing the inert gas flow rate or in the second half of the insulation period, and then immediately switched back to a pure inert atmosphere after a short exposure. This periodic pulse of trace hydrocarbon gas can promote continuous and stable nucleation of crystal nuclei without significantly increasing the grain size, thereby achieving more precise particle size control and crystal form optimization. At the same time, by strictly controlling the atmosphere switching time and gas ratio, excessive grain growth can be suppressed, thereby obtaining a finer and more uniform distribution of TiC nanoparticles.

[0068] S4, step of selectively etching excess carbon layer:

[0069] a. Preparation and loading:

[0070] The solid product (TiC product containing excess amorphous carbon) after high-temperature carbonization and furnace cooling is taken out from the high-temperature furnace and quickly transferred to another treatment furnace (or the same furnace chamber with changed atmosphere and temperature settings) under the protection of an inert atmosphere. To avoid the adsorption of air or moisture, the loading should be carried out in an inert atmosphere glove box or under the conditions of vacuuming and then filling with argon.

[0071] b. Atmosphere preparation:

[0072] Fill the treatment furnace with protective gas (such as Ar or N2) to ensure that there is no oxygen or water vapor remaining in the system. The pressure and flow rate at this time can be adjusted according to the performance of the equipment, generally maintaining normal pressure or slightly below normal pressure.

[0073] If H2 atmosphere treatment is used, the furnace chamber can be repeatedly charged and discharged with Ar or N2 to ensure that the residual oxygen content is extremely low, and then a small amount of H2 is introduced into the furnace. The volume fraction of H2 can be 5-20%, and the rest is protective gas (such as Ar) to obtain a slightly reducing dilute hydrogen environment. The gas flow rate is accurately controlled by a gas mass flow meter (MFC).

[0074] c. Heating and keeping warm:

[0075] The mixture is heated from room temperature to a temperature range of 300 to 500°C at a heating rate of 3 to 10°C / min (the temperature range may be appropriately selected according to the excess carbon content and the surface characteristics of the particles, such as 350°C or 450°C).

[0076] After reaching the target temperature, maintain the temperature for 0.5 to 2 hours. During this period, H2 reacts slightly with the amorphous carbon on the solid surface under heating conditions (such as generating CH4 or other volatile small molecules), thereby selectively etching, stripping or reducing the excess carbon layer and reducing the free carbon content. During this process, a low flow rate of H2 / Ar mixed gas should be maintained, and the gas flow rate is usually in the range of 100 to 500 mL / min (depending on the furnace size and sample amount) to ensure the stability of the reaction gas partial pressure in the furnace chamber.

[0077] d. Process monitoring and safety measures:

[0078] During the etching process, the exhaust gas composition can be monitored by an online gas analyzer (such as MS or GC). If changes in the concentration of products such as CH4, CO, CO2, etc. are detected, the progress of the etching reaction can be judged.

[0079] Strictly prevent hydrogen from mixing with air. During operation, ensure that the furnace body is well sealed and the exhaust port leads to a safe exhaust system to eliminate the risk of explosion.

[0080] e. Cooling and termination treatment:

[0081] After the insulation is completed, the heating is stopped and the temperature is naturally or controlled to room temperature under the flow of inert atmosphere. During the cooling process, the protective gas is continuously introduced to prevent oxygen reflux from causing product oxidation.

[0082] When the temperature returns to room temperature, turn off the gas flow and keep the furnace inert. Before taking out the product, briefly evacuate the furnace or repeatedly fill it with protective gas to ensure a pure environment.

[0083] f. Material discharging and inspection:

[0084] Before opening the furnace cover, protective gas can be introduced again to ensure a safe sampling environment without the risk of secondary oxidation. Take out the etched samples and verify the reduction of free carbon phase by X-ray diffraction (XRD) or Raman spectroscopy analysis; transmission electron microscopy (TEM) can further observe the grain size and surface state of TiC particles to confirm that amorphous carbon has been significantly reduced and the particle size distribution is more uniform.

[0085] S5. Post-processing steps:

[0086] After the step of selectively etching the excess carbon layer is completed, the protective gas is charged and discharged multiple times to remove the residual H2 gas. After the furnace temperature is cooled to room temperature, the furnace is opened to take out the material, and nano-titanium carbide particles of a predetermined size are obtained after sieving, and finally nano-TiC powder with an average particle size of 10 to 50 nm and uniform particle size distribution is obtained.

[0087] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing nano titanium carbide particles, characterized in that: The following steps are involved: S1. Precursor synthesis steps: The titanium source compound and the organic ligand are mixed and reacted in a solvent, and the reaction temperature and reaction time are controlled to form a titanium-containing metal organic framework, i.e., a MOF precursor; S2. Precursor pretreatment steps: The MOF precursor obtained in step S1 is centrifuged, washed and dried at a temperature of 60 to 120° C. for a drying time of 6 to 24 hours to obtain a uniformly refined MOF precursor powder; S3, step of graded heating and pyrolysis: The dried MOF precursor powder is placed in a heating furnace, with protective gas as the base gas, and a trace amount of control gas is introduced at a specific stage to achieve dynamic atmosphere control, complete graded heating pyrolysis, and obtain a fine and uniform distribution of nano-TiC grains; S4, step of selectively etching excess carbon layer: After the furnace temperature is naturally cooled to a predetermined temperature, the treatment furnace is filled with protective gas, and then H2 gas is introduced into the furnace, with a volume fraction of H2 of 5 to 20%, to obtain a slightly reducing dilute hydrogen environment; After heating to a predetermined temperature, the temperature is maintained, so that H2 reacts slightly with amorphous carbon on the solid surface under heating conditions, thereby selectively etching the excess carbon layer and reducing the free carbon content; S5, post-processing steps: After the step of selectively etching the excess carbon layer is completed, the protective gas is charged and discharged multiple times to remove the residual H2 gas. After the furnace temperature is cooled to room temperature, the furnace is opened to take out the material, and nano-titanium carbide particles of a predetermined size are obtained after sieving.

2. A method for preparing nano-titanium carbide particles according to claim 1, characterized in that: Step S1 specifically includes: a reaction temperature of 25 to 80° C., a reaction time of 12 to 48 hours; a solvent of a mixture of one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP) or dimethyl sulfoxide (DMSO); The titanium source is TiCl4 or Ti(OR)4, wherein R is a C1-C4 alkyl group, and the organic ligand is selected from a multidentate ligand containing a carboxyl group, a hydroxyl group or a nitrogen coordination group; the grain size of the obtained titanium-containing metal organic framework MOF precursor is 100-500nm.

3. A method for preparing nano-titanium carbide particles according to claim 1, characterized in that: Step S3 specifically includes: S31, low temperature desorption and atmosphere control stage: After heating to a predetermined temperature, the temperature is maintained, and then a H2 / Ar mixed gas is introduced to reduce the surface of the titanium precursor in the MOF precursor and reduce the impurity oxygen content; S32, medium temperature orderly deconstruction and precursor phase regulation stage: The temperature is raised to a predetermined temperature again and then kept warm, during which the total system pressure is intermittently reduced to discharge small molecular gaseous products; S33, high temperature directional carbonization and particle size suppression stage: The temperature is raised to the predetermined temperature again and then kept warm. In the second half of the warm-keeping period, hydrocarbon gas is quantitatively introduced at a rate of <0.5 vol%. After a short exposure, the protective atmosphere is switched back.

4. A method for preparing nano-titanium carbide particles according to claim 3, characterized in that: Step S31 is specifically as follows: The temperature is raised from room temperature to 200-300°C at a heating rate of 1-5°C / min, and kept at this temperature for 0.5-2 hours to remove the residual solvent in the pores; In the second half of the heat preservation, 0.1-1 vol% H2 / Ar mixed gas can be introduced in a pulsed manner to slightly reduce the surface of the titanium precursor in the titanium-containing metal organic framework and reduce the impurity oxygen content, thereby reducing oxide inclusions for the subsequent carbonization process.

5. The method for preparing nano-titanium carbide particles according to claim 3, characterized in that: Step S32 is specifically as follows: continue to raise the temperature to 500-700° C. at a rate of 3-10° C. / min, and keep the temperature for 1-3 hours. During the heat preservation period, the total pressure of the system is intermittently reduced to allow small molecular gaseous products to be continuously discharged.

6. A method for preparing nano-titanium carbide particles according to claim 5, characterized in that: In step S32, intermittently reducing the total system pressure means: pumping the pressure to 50-80% of the current original pressure every 30 minutes, and maintaining the pumping for 5-10 minutes, then stopping the pumping, and pumping again after 30 minutes.

7. The method for preparing nano-titanium carbide particles according to claim 3, characterized in that: Step S33 is specifically as follows: The temperature is raised to 800-1200°C at a rate of 5-10°C / min, and kept at this temperature for 2-6 hours to allow Ti and carbon to react in situ to form TiC nano-grains. In the second half of the holding period, hydrocarbon gas is quantitatively introduced at a rate of <0.5 vol%, and after a short exposure of 5-10 minutes, the pure protective atmosphere is switched back; the hydrocarbon gas is CH4, C2H2 or a mixture of CH4 and C2H2.

8. The method for preparing nano-titanium carbide particles according to claim 1, characterized in that: Step S5 is specifically as follows: S51, after the furnace temperature is naturally cooled to 100° C., the treatment furnace is filled with protective gas, and then H2 gas is introduced into the furnace, with a volume fraction of H2 of 5 to 20%, to obtain a slightly reducing dilute hydrogen environment; S52. Starting from 100°C, heat to 300-500°C at a heating rate of 3-10°C / min, and then keep warm for 0.5-2 hours to allow H2 to react with amorphous carbon on the solid surface under heating conditions, selectively etch the excess carbon layer, and reduce the free carbon content.

9. The method for preparing nano-titanium carbide particles according to claim 1, characterized in that: The protective gas is one of pure argon, pure nitrogen, and a mixture of nitrogen and argon.

10. A nano titanium carbide particle, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Novel catalyst based on metal organic framework material and preparation method and application of novel catalyst

    CN106582887A

  • Preparing method of low-boron-content SiC fiber

    CN110106583A

  • Superfine tungsten carbide powder as well as preparation method and application thereof

    CN116143123A

  • Hybrid composite comprising metal-organic framework and two-dimensional sheet

    KR102366563B1